Changes in corneal endothelial cells after trabeculectomy and EX-PRESS shunt: 2-year follow-up - Omatsu, Saki (BMC Ophthalmol, 2018)
BACKGROUND: To compare trabeculectomy and EX-PRESS device implantation procedures for treating glaucoma and evaluate changes in corneal endothelial cell density (CECD). METHODS: This study prospectively evaluated changes in the CECD in 60 eyes of 60 patients who underwent trabeculectomy and 50 eyes of 45 patients who underwent EX-PRESS device implantation. Baseline patient data recorded included age at surgery, sex, type of glaucoma medications, and lens status. Using a noncontact specular microscope, corneal specular microscopy was performed preoperatively at the central cornea and then at 6, 12, 18 and 24 months after surgery. CECD before and after surgery was compared using a paired t-test. RESULTS: There was a significant decrease in the IOP and number of antiglaucoma medications in both groups after the surgery. The mean CECD in the trabeculectomy group was 2505 ± 280 cells/mm(2) at baseline, while it was 2398 ± 274 cells/mm(2) (P < 0.001), 2349 ± 323 cells/mm(2) (P < 0.001), 2293 ± 325 cells/mm(2) (P < 0.001), and 2277 ± 385 cells/mm(2) (P = 0.003) at 6, 12, 18, and 24 months, respectively. However, the CECD in the EX-PRESS group was 2377 ± 389 cells/mm(2) at baseline, while it was 2267 ± 409 cells/mm(2) (P = 0.007), 2292 ± 452 cells/mm(2) (P = 0.043), 2379 ± 375 cells/mm(2) (P = 0.318), and 2317 ± 449 cells/mm(2) (P = 0.274) at 6, 12, 18, and 24 months, respectively. CONCLUSIONS: As compared to trabeculectomy, EX-PRESS device implantation appears to be a safer procedure with regard to the endothelial cell loss risk.